Effect of two phytases at two doses on performance and phytate degradation in broilers during 1-21 days of age. - Yueming Dersjant-Li; Roger Davin; Trine Christensen; Cees Kwakernaak (PLoS ONE)
The effect of two microbial phytases at two dose-levels on performance and apparent ileal digestibility (AID) of nutrients in broilers fed European-type diets was studied. A total of 1,200 d-old Ross 308 male broilers were randomly assigned to 5 treatments with 30 birds/pen and 8 pens/treatment. A nutritionally adequate positive control (PC) diet was tested against 4 experimental diets containing reduced total P, retainable P, Ca and Na as per the recommended nutritional contribution for Buttiauxella phytase (Phy B) at 1,000 FTU/kg (-1.87 g/kg, -1.59 g/kg, -1.99 g/kg and -0.4 g/kg vs. PC, respectively). Experimental diets were supplemented with Phy B at 500 FTU/kg or 1,000 FTU/kg, or Citrobacter phytase (Phy C) at 1,000 FTU/kg or 2,000 FTU/kg. Diets were based on corn, soybean meal, rapeseed meal and sunflower meal and formulated by phase (starter 1-10 d, grower 11-21 d) in crumbled or pelleted form. Overall (d 1-21), at 1,000 FTU/kg, birds fed Phy C exhibited lower BWG (-2.7%), FI (-3.4%) and tibia ash (-2.2%) vs. PC (P < 0.05), and reduced BWG (-3.6%), FI (-3.9%) and tibia ash (-1.8%) vs. Phy B (P < 0.05). Phy B at 1,000 FTU/kg and Phy C at 2,000 FTU/kg maintained performance equivalent to the PC. Digestibility of Ca did not differ among phytase treatments but at 1,000 FTU/kg AID P was greater with Phy B than Phy C (72.3% vs. 62.7%, P < 0.05). Ileal phytate (myo-inositol hexakisphosphate, IP6) digestibility was greatest with Phy B at 1,000 FTU/kg which was higher than Phy C at 1,000 FTU/kg (87.6 vs. 60.6%, P < 0.05). The findings indicate a higher phytate degradation rate of Phy B than Phy C at equivalent dose-level and this is correlated to the performance of the broilers.